Deregulated expression of A1, Bcl-2, Bcl-xL, and Mcl-1 antiapoptotic proteins and Bid, Bad, and Bax proapoptotic genes in polycythemia vera patients - Elainy Patricia Lino Gasparotto; Raquel Tognon; Aline Fernanda Ferreira; Gislane Lelis Vilela Oliveira; Patrícia Vianna Bonini Palma; Maria Aparecida Zanichelli; Elizabeth Xisto Souto; Carlos Eduardo Engel Velano; Belinda Pinto Simões; Rita de Cassia Viu Carrara; Simone Kashima; Dimas Tadeu Covas; et al. (Universidade de São Paulo, 2011)
Apoptosis deregulation might have a role in the pathophysiology of polycythemia vera (PV). This study evaluated Bcl-2 molecule expression in CD34+ cells and leukocytes in 12 PV patients. Gene expression was investigated by real time PCR using SybrGreen Quantitect kit and protein expression was evaluated by western-blotting. JAK2 V617F mutation was detected according to Baxter et al (2005). CD34+ cells from PV patients presented higher levels of A1 and Mcl-1 expression (median: 22.6 and 5.2, respectively) in comparison with controls (0.9 and 0.5, p=0.004 and p=0.020); while Bcl-2 and Bcl-xL expression decreased in PV patients (0.18 and 1.19) compared with controls (1.39 and 2.01, p=0.006 and p=0.020). CD34+ cells in PV patients showed an elevated Bid expression (14.4) in comparison with healthy subjects (1.0; p=0.002). Patients' leukocytes showed an A1 augmentation (7.41, p=0.001) and a reduced expression of Bax (0.19; p=0.040) and Bad (0.2; p=0.030). There was no correlation between JAK2 V617F allele burden and molecular expression. PV patients showed alterations in Bcl-2 members' expression, which may interfere with control of apoptotic machinery and contribute to disease pathogenesis. A desregulação da apoptose parece participar da fisiopatologia da policitemia vera (PV). Este estudo avaliou a expressão das moléculas da família Bcl-2 em células hematopoéticas CD34 + e leucócitos de 12 pacientes com PV. Foram realizados: a quantificação da expressão gênica por PCR em tempo real utilizando kit Sybrgreen Quantitect, avaliação da expressão de proteínas por western-blot e detecção da mutação JAK2 V617F segundo Baxter et al. (2005). Células CD34 + dos pacientes com PV apresentaram maior expressão de A1 e Mcl-1 (mediana: 22,6 e 5,2, respectivamente) em comparação com controles (0,9 e 0,5, p = 0,004 e p = 0,020) e expressão de Bcl-2 e Bcl-xL diminuída nestes pacientes (0,18 e 1,19) em relação aos controles (1,39 e 2,01, p = 0,006 e p = 0,020). Células CD34 + dos pacientes com PV mostraram expressão elevada de bid (14,4) em comparação aos controles (1,0; p = 0,002). Leucócitos dos pacientes mostraram aumento de A1 (7,41, p = 0,001) e expressão reduzida do Bax (0,19; p = 0,04) e Bad (0,2; p = 0,030). Não houve correlação entre percentagem de alelos JAK2 V617F mutados e expressão molecular. Pacientes com PV apresentaram alterações na expressão de moléculas Bcl-2 que podem interferir no controle da apoptose e contribuir para a patogênese da doença.